Evaluation of a Program to Develop Research Skills in Health Sciences Students - Centellas, Yudy Yaneth Tapia; Condori, Lizbeth Acero; Maquera, Nelly Beatriz Quispe; Chirinos, Kandy Faviola Tuero; Quispe, Betsy Quispe; Betancur, Heber Nehemias Chui (O Mundo da Saúde, 2024)
The development of investigative skills is a challenge in higher education, as university students must be capable of generating knowledge and solving problems. This study aimed to evaluate the development of these skills in university students in Puno, specifically health sciences students. The research adopted a quasi-experimental design, suitable for measuring changes in a group before and after the intervention. To assess the effectiveness of the investigative skills development program, the Wilcoxon signed-rank test was used—a robust statistical tool for comparing two related samples when data normality cannot be assumed. The study involved 111 biomedical students who participated in a program designed to enhance their research skills. The results reveal significant findings in various areas of research skill development. Notably, there was a strong impact on structural development, with a Z-value of -8.776 (P<0.01), while sociability and dissemination showed a Z-value of -8.918 (P<0.01), suggesting that these factors play an important role in interaction effectiveness. Digital technology, with a Z-value of -9.027 (P<0.01), emphasizes the importance of digital tools in the research context. Finally, specialty and technological discipline displayed a Z-value of -8.904 (P<0.01), underscoring the relevance of specialization in the technological field. The program for developing research skills proved to be effective.